Factors associated with failed extubation in extremely low birth premature newborn: A retrospective observation study - Ibrahim , Linda; Salama, Husam Eldin Mokhtar; Gonzales Baldovino, Wendy; Dias , Laveena; Yogore , Maricar Nito (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Most of the extremely low birth weights (ELBW) are intubated in the delivery room or soon after.  Achieving successful extubation is one of the most critical milestones in managing these newborns. This study aimed to evaluate the extubation patterns of ELBW newborns (23 and 27 gestation weeks).Methods: This population-based retrospective study was conducted at a tertiary neonatal intensive care unit (NICU) in Qatar for 30 months. Data was collected from electronic medical records.Results: The study comprised 73 ELBW newborns who were successfully extubated and 55 had to be re-intubated, resulting in a failure rate of 42% (55/128). Logistic regression analysis revealed that weight at extubation was significant (AUC = 0.693), birth weight (AUC = 0.702), gestational age (AUC = 0.707), and age at initial extubation are significant predictors of extubation outcome (p < 0.0001). Active patent ductus arteriosus and extubation within < 24 hours after birth caused extubation failure. The administration of two doses of prenatal steroids and one dosage of surfactant exhibited a significant difference between the two groups (P = 0.027 and 0.001, respectively). Neonatal infection was the primary reason for re-intubation after 14 days of life.Conclusions: The most common risk factors for failed extubation were gestational age of 23–25 weeks, active patent ductus arteriosus, extubation occurring in less than 24 hours after birth, and birth weight under 800 grams. The 7–14-day observation window was the most optimal time frame for reporting the reintubation rate.